2021
DOI: 10.1002/adsu.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Efficient Catalysts Based on La‐Doped Ceria‐Supported Nickel Nanoparticles for rWGS Reaction. Influence of Ni Loading

Abstract: to a few processes: syntheses of urea, salicylic acid, and polycarbonates, but these only correspond to a few percentage of the potential CO 2 suitable to be converted into chemicals and/or fuels. [1] Conversion of CO 2 into CO by catalytic hydrogenation has been recognized as one of the most promising processes for CO 2 utilization. Synthesis gas (syngas) could then be used to produce hydrocarbons or oxygenated hydrocarbons via Fischer-Tropsch reaction, as well as for the synthesis of methanol. This is a basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Spin-polarized DFT calculations were performed to gain insights into the roles of the metal and oxide phases of low-loaded nickel-ceria model catalysts in the activation of CO 2 as well as the H 2 dissociation and subsequent H diffusion that ultimately leads to the formation of CO and H 2 O. Previous experimental results , indicate that the system consists of nickel metal nanoparticles supported on a La-doped ceria with different degrees of reduction. We chose a flat Ni 4 cluster structure supported on the fully oxidized CeO 2 (111) and on the fully reduced Ce 2 O 3 (0001) surfaces as representative models of low-loaded ceria-supported nickel catalysts, which illustrate accurately many of the essential atomic-scale features that control the catalyst stability, electronic structure, and surface reactivity, as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin-polarized DFT calculations were performed to gain insights into the roles of the metal and oxide phases of low-loaded nickel-ceria model catalysts in the activation of CO 2 as well as the H 2 dissociation and subsequent H diffusion that ultimately leads to the formation of CO and H 2 O. Previous experimental results , indicate that the system consists of nickel metal nanoparticles supported on a La-doped ceria with different degrees of reduction. We chose a flat Ni 4 cluster structure supported on the fully oxidized CeO 2 (111) and on the fully reduced Ce 2 O 3 (0001) surfaces as representative models of low-loaded ceria-supported nickel catalysts, which illustrate accurately many of the essential atomic-scale features that control the catalyst stability, electronic structure, and surface reactivity, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Among the possible methods to prepare these ceria-supported Ni catalysts, we have selected the solution combustion synthesis (SCS) method. Using a patented specific protocol that includes, among other conditions, a controlled ratio between fuel and metal precursors, a porous and finely particulate metal oxides materials with very high macroporosity and the formation of Ni particles in the metallic state are obtained. These critical points help to promote heat and mass transport and prevent the formation of hot-spots during the catalytic reaction. A deep characterization using X-ray and neutron diffraction, Raman spectroscopy, in situ NAP-XPS, and electron microscopy, in combination with DFT calculations, was performed and correlated with the reaction performance, highlighting the key parameters that control reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, these catalysts’ reduction temperatures are lower than those of the unmodified ones, indicating better metal phase dispersion because CeO 2 reduces the weakening of the NiO–support interaction and increases the ability to disperse NiO on the HA surface. Besides that, Figure b also shows that the ceria-doped catalysts have weak reduction signals above 600 °C; these reduction signals belong to the reduction process of the phases of NiO–CeO 2 interaction or surface CeO 2 in the doped catalysts . The content of the CeO 2 doping is low (4–8%), so the reduction signal is not high.…”
Section: Results and Disussionmentioning
confidence: 92%
“…Besides that, Figure 7 b also shows that the ceria-doped catalysts have weak reduction signals above 600 °C; these reduction signals belong to the reduction process of the phases of NiO–CeO 2 interaction or surface CeO 2 in the doped catalysts. 43 The content of the CeO 2 doping is low (4–8%), so the reduction signal is not high. When compared to other catalysts, the maximum reduction peaks of 10Ni6Ce/HA are in the lowest temperature region.…”
Section: Results and Disussionmentioning
confidence: 99%
“…Based on the efficient photothermal system, the catalyst has become the key to realizing applicable photothermal RWGS. Scientists have found that various non-precious metal based catalysts are active for RWGS, including Ni-, 15,16 Cu-, [17][18][19] In-, 20 and Co-based catalysts. 21 Because RWGS operates in a hydrogen rich environment, the metal species in those catalysts are metallic or in low oxidation state.…”
Section: Introductionmentioning
confidence: 99%